Fabrication of a Resonant Photoacoustic Cell for Samples Study - Kapil, J.C.; Joshi, S.K.; Rai, A.K. (Defence Science Journal, 2004)
Nondestructive treatment of a sample in photoacoustic spectroscopy is helpful in the study of thermal and optical properties of ice and snow. In the present study, a  low-temperature resonant photoacoustic cell, based on Helmholtz resonator model, has been designed and fabricated for the study of samples like ice or snow. Its performance has also been studied using carbon black as a standard sample and various other samples like water, ice, glass, plexi-glass, polycarbonate, etc. Thermal diffusivity of ice, water, and many other transparent materials has been determined by varying chopping frequency and recording corresponding phase changes in the photoacoustic signal. The results obtained are in good agreement with those predicted by Rosencwaig-Gersho (R-G)' theory.